Dendritic Cell Markers and PD-L1 are Expressed in Mediastinal Gray Zone Lymphoma. Issue 10 (November 2018) - Pelland, Kevin; Mathews, Stephanie; Kamath, Anitha; Cohen, Paul; Hudnall, S. David; Cotta, Claudiu V.; Xu, Mina L.
Abstract : Aims: Mediastinal gray zone lymphoma (MGZL) is a rare entity with morphologic, immunophenotypic, and genetic features intermediate between classic Hodgkin lymphoma (CHL) and primary mediastinal large B-cell lymphoma (PMBL). It is challenging to differentiate from CHL and PMBL. A specific dendritic cell gene expression profile can distinguish CHL and MGZL from PMBL. We hypothesized that the dendritic markers fascin and CD123 may be helpful in distinguishing MGZL from CHL and PMBL. We also investigated programmed death-ligand 1 (PD-L1) expression in MGZL, which may have therapeutic significance in this difficulty to treat tumor. Methods: Representative sections from 89 CHL, 20 PMBL, and 7 MGZL cases were stained for fascin, CD123, and PD-L1, and scored on a scale from 0 to 3+. Most (71%) MGZLs stained for CD123, as well as some (23%) CHLs, and few (11%) PMBLs. All MGZLs stained for fascin, as well as most (90%) CHLs, and approximately half (53%) of the PMBLs. PD-L1 was positive in all MGZLs, most (77%) CHLs and most (66%) PMBLs. Conclusions: Our study is the first to show CD123 is positive in a subset of formalin-fixed, paraffin-embedded MGZLs and CHLs, in contrast to PMBL which is largely negative. Staining for fascin was not significantly different between the lymphomas, but was less likely to be positive in PMBL. These findings suggest a role for CD123 and fascin in supporting diagnoses of MGZL and CHL, and in ruling out PMBL. By immunohistochemistry, PD-L1 is positive in MGZL, pointing to its therapeutic potential.